α-Lipoic acid: a potential regulator of copper metabolism in Alzheimer’s disease - Kirss, Sigrid; Reinapu, Anette; Kabin, Ekaterina; Smirnova, Julia; Tõugu, Vello; Palumaa, Peep (Frontiers in Molecular Biosciences, 2024)
Alzheimer's disease (AD) is characterized by classic hallmarks such as amyloid plaques and neurofibrillary tangles, however, intensive research has broadened its scope to explore additional underlying mechanisms. Notably, disruptions in metal homeostasis, particularly involving copper, have gained significant attention. In AD pathology, an imbalance is evident: there is an excess of extracellular copper alongside a deficiency in intracellular copper in brain tissue. Our previous work demonstrated that α-lipoic acid (LA) can effectively shift copper from the extracellular space to the intracellular environment in a neuronal cell model. However, the precise mechanism of action and role of LA in copper metabolism remained elusive. In this study, we compared the cellular effects of LA with those of different synthetic copper-binding ligands: diethyldithiocarbamate (DETC), clioquinol (CQ), D-penicillamine (D-PA) and elesclomol (ES). Using differentiated SH-SY5Y cell culture as a neuronal model, we found that, unlike other synthetic compounds, natural ligand LA is not toxic in the presence of extracellular copper, even at high doses. LA gradually increased intracellular copper levels over 24 hours. In contrast, DETC, CQ, and ES acted as fast copper ionophores, potentially explaining their higher toxicity compared to LA. D-PA did not facilitate copper uptake into cells. We demonstrated that a slow increase of LA inside the cells is enhanced in the presence of copper. Furthermore, the ability of LA to modulate the equilibrium of extra-and intracellular copper was evident when we added copper isotope 65 Cu. The ratio of copper isotopes changed rapidly, reflecting the impact of LA on the equilibrium of copper distribution without affecting the copper transport network. Our results provide compelling evidence that α-lipoic acid holds promise as a non-toxic agent capable of normalizing copper metabolism in Alzheimer's disease.